Identification of Positive Trends in Physical Literacy Among Primary School Students: A Longitudinal Study for 2024–2025 - Ahmad Winoto; Adi S (Universitas Negeri Semarang, 2025)
Physical literacy is a holistic ability that encompasses physical, cognitive, and affective dimensions, playing an important role in encouraging lifelong participation in physical activities. This study aims to analyze changes in the physical literacy of elementary school students in Gunungpati District, Semarang City, over a period of two academic years. The research design used was a pure longitudinal study involving public elementary school students (n = 99) who were selected purposively. Physical literacy was measured using a combination of objective tests (TIAMSA, PACER, 30-second sit-ups) for the physical dimension and perception questionnaires for the cognitive and affective dimensions. The analysis was conducted using a paired sample t-test for inter-year comparisons and a Linear Mixed Model (LMM) to control for individual and school variations. The results showed a significant increase in total physical literacy scores (Mean Difference = p < 0.05), with the most consistent upward trend in the physical dimension (p < 0.01), while the cognitive and affective dimensions showed fluctuations and were not always significant (p > 0.05). LMM analysis confirmed the effect of time on physical literacy, but there was a lack of parallel development across dimensions. In conclusion, students' physical literacy improved, especially in physical abilities, while non-physical dimensions required special attention. This study is novel because it combines objective and subjective assessments in a longitudinal design in Indonesia and provides important empirical insights for holistic physical education policy.